2020
DOI: 10.37398/jsr.2020.640103
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Vegetation Response to Seasonal Rainfall in the Gomati River Basin (India) using Earth Observation Data Sets

Abstract: Present study evaluates the vegetation responses towards the rainfall variability in the Gomati basin during 1901-2015. To accomplish the same, high resolution observed daily gridded rainfall data from India Meteorological Department (IMD) was analysed using non-parametric trend test. The long-term rainfall showed significant decreasing trend (α=0.05) which varied from -0.96 to -4.89 per year. Identified trends in rainfall were then evaluated in tandem with the basin-wide changes in the vegetation signatures d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…At the temporal scale, CCA triplots showed that the density, frequency, cover, and important value of vegetation were highest in spring, followed by summer. It may be due to lower dust concentration in spring and summer which supported plant growth as revealed by (Prajapati and Tripathi, 2008) and high soil moisture in July followed by spring which favours vegetation growth as revealed by the study of (Bhatt et al, 2020) on impact of seasonal rainfall on vegetation dynamics.…”
Section: Ecological Analysis Of Vegetationmentioning
confidence: 93%
“…At the temporal scale, CCA triplots showed that the density, frequency, cover, and important value of vegetation were highest in spring, followed by summer. It may be due to lower dust concentration in spring and summer which supported plant growth as revealed by (Prajapati and Tripathi, 2008) and high soil moisture in July followed by spring which favours vegetation growth as revealed by the study of (Bhatt et al, 2020) on impact of seasonal rainfall on vegetation dynamics.…”
Section: Ecological Analysis Of Vegetationmentioning
confidence: 93%
“…As the Gomati basin has been documented to have undergone dry years (Bhatt et al, 2020), it is probable that some of the rainfall deficit might have impacted the hydrological cycle in the basin. Here, correlation analysis (Section 3.5) method used by Wu et al (2021), was relied…”
Section: Drought Propagationmentioning
confidence: 99%
“…Similarly, RAI, SSI, SRI, SSMI and so forth, individually lack capabilities to evaluate complex multidimensional phenomenon that any drought is due to, because of their single parameter based construct (Chen et al, 2020). The Gomati River system has been the focus of water quality investigations during the last two decades (Bhatt et al, 2020). The dimension of hydrology has only recently been considered for research, especially in terms of basin's response to variability in climate (Abeysingha et al, 2015;Mali et al, 2015Mali et al, , 2017Mali et al, , 2018Singh et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, vegetation dynamics and strong associations between vegetation and climate change have been reported in various watersheds of the world [ 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. Olivares et al [ 34 ] reviewed the impact of climate change on lowland rainforests in the Amazon basin, and concluded that warming will limit plant species survival by decreasing vegetation productivity.…”
Section: Introductionmentioning
confidence: 99%